PENGARUH PERSONAL SELLING DAN HARGA TERHADAP MINAT BELI KAMAR PADA GARUDA PLAZA HOTEL MEDAN - Maulani, Kiki (Jurnal Ilmiah Akomodasi Agung, 2024)
The purpose of this research was to determine there is an effect of personal selling and price on the interest in buying hotel room at Garuda Plaza Hotel Medan in period of 2021. The sample of this research are 89 hotel guest. Using sample census technique, which is a sampling technique if all members of population are used as samples. Data analysis used Linear Regression test, while data processing using SPSS. The results of this research that partially the effect of personal selling and price has significant effect on the interest in buying hotel room at Garuda Plaza Hotel Medan